Exploring the perceived value of social practice theories for business-to-business marketing managers. Issue 5 (8th August 2016) - Lowe, Sid; Rod, Michel; Kainzbauer, Astrid; Hwang, Ki-Soon
Abstract : Purpose: Drawing on sociological theories of Giddens, Bourdieu and Goffman, the purpose of this paper is to explore how different relationships are characterized between actors in interaction and determine whether social theories of practice resonate as being practical to managers. Design/methodology/approach: In the empirical investigations, the authors employ the Delphi method whereby the authors "elevate" six highly experienced marketing practitioners in Dubai and Bangkok, each in different industries and from different cultural backgrounds, to designated "expert" positions in exploring the practical relevance of the practice-based theories of Bourdieu, the dramaturgy of Goffman and the structuration theory of Giddens in understanding practical experiences of managing in business-to-business networks. Findings: The results show that aspects of these theories are consistent with practitioners' experiences in many ways but the theories themselves do not appear to resonate with the modernist practical consciousness of the participants as being particularly pragmatic or practically useful except as resources they could selectively borrow from as bricoleurs of changing action. Originality/value: Social practice theories appear rather too abstract and complex to practical actors. It is therefore paradoxical that social practice theories do not appear as sufficiently "handy" or "ready to hand" in Heidegger's (1962) terms; being in need of translation into practical usefulness. It would appear that social practice theories can be a useful analytical vehicle for the academic analyst but cannot resonate with the modernist consciousness of the practical actor.